Reducing Calf Mortality in Ethiopia - Johanna T. Wong; Jennifer K. Lane; Fiona K. Allan; Gema Vidal; Ciara Vance; Meritxell Donadeu; Wendi Jackson; Veronica Nwankpa; Shubisa Abera; Getnet Abie Mekonnen; Nigatu Kebede; Berhanu Admassu; et al. (Animals, 2022)
Morbidity and mortality of young stock present economic and production challenges to livestock producers globally. In Ethiopia, calf morbidity and mortality rates, particularly due to diarrhea and respiratory disease, are high, limiting production, incomes, and the ability of farmers to improve their livelihoods. In this paper, we present findings from the combined experience of the Young Stock Mortality Reduction Consortium, which conducted epidemiological and intervention testing in calves across three production systems. This innovative alliance identified Cryptosporidium parvum and E. Coli K99 as the most common causes of diarrhea in pastoral and peri-urban calves; Strongyloides spp. as the most common fecal parasite in mixed crop–livestock and peri-urban calves; and bovine adenovirus, parainfluenza virus-3, and bovine respiratory syncytial virus as the most common respiratory pathogens in peri-urban calves. Furthermore, by improving producer knowledge with respect to fundamental livestock husbandry, feeding, housing, and neonatal care practices, calf mortality risk across production systems was reduced by 31.4 to 71.4% compared to baseline (between 10.5 and 32.1%), whereas risk of diarrhea was reduced by 52.6–75.3% (baseline between 11.4 and 30.4%) and risk of respiratory disease was reduced by 23.6–80.8% (baseline between 3.3 and 16.3%). These findings have informed scaling strategies and can potentially contribute to improved livestock productivity and human livelihoods in Ethiopia.